Sapaan sebagai Ungkapan Fatis pada Masyarakat Sunda - Zhafira Ramadhyanti, Zahra; Arimi, Sailal (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Indonesia is a country with various cultures. The way people use language can reflects cultural value. Language has specific functions, and one of them is a phatic function. The phatic form is used to maintain social bonds between speakers and hearers. Sundanese is one of the regional languages in Indonesia where many phatic forms are found, one of them is the use of addressed terms. In Sundanese culture, several forms of addressed terms are found, which are identified as phatic forms. In the culture of the Sundanese people, several forms of address terms are found, which are identified as phatic expressions. In collecting the data, observation is done to find natural data in the forms of address terms used by adolescent and adult speakers in Bandung, West Java. A survey using questionnaire was also conducted to validate the data obtained through observation. Based on the analysis and discussion, this study shows that there are several functional differences in the use of address terms as phatic expression in the domain of friendship, family, and strangers analyzed based on age perspective. The use of address terms as phatic expression reflects the culture of Sundanese people that uphold politeness values. Keywords: Address terms; Phatic expression; Sundanese speech community; Sundanese language.